Belize. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Belize during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as technologies, food security, marketing, rural development, public policies, nutritional security, biodiversity and resilience against climate change. climate change. Finally, work was done in field schools, organic agriculture, natural resource management, and in the value chains of corn, beans, and sugar cane.